Co-Operatives in a Post-Growth Era : Creating Co-operative Economics. - Novkovic, Sonja; Webb, Tom (Zed Books, 2014)
An essential introduction to the co-operative business model as a sustainable and equitable alternative to the current growth-obsessed economic paradigm.